Biomedical Engineering Systems and Technologies 7th International Joint Conference, BIOSTEC 2014, Angers, France, March 3-6, 2014, Revised Selected Papers - Plantier, Guy; Schulz, Tanja; Fred, Ana; Gamboa, Hugo (Communications in Computer and Information Science, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 7th International Joint Conference on Biomedical Engineering Systems and Technologies, BIOSTEC 2014, held in Angers, France, in March 2014. The 25 revised full papers presented were carefully reviewed and selected from a total of 362 submissions. The papers cover a wide range of topics and are organized in topical sections on biomedical electronics and devices; bioimaging; bioinformatics models, methods and algorithms; bio-inspired systems and signal processing; health informatics.